Feasibility of Computed Tomography Pulmonary Angiography with Low Flow Rates - Gossner,J.
Computed tomography pulmonary angiography (CTPA) is the imaging test of choice in suspected pulmonary embolism. High flow rates for the administration of contrast medium are recommended, but these cannot be achieved in a number of patients due to poor peripheral venous access or when using certain central venous catheters. This small feasibility study has examined the CTPA data in a set of 22 patients in whom contrast medium was given at low flow rates (2.0 or 2.5 mL/s). Subjectively, all but one of the patients was judged to be diagnostic. Objectively, enhancement values ≥200 HU were reached in 92% of the examined central vessels (pulmonary trunk, main pulmonary arteries, and lobar arteries). In conclusion, even with a low injection rate CTPA is of diagnostic value in most patients.